CROSS-CULTURAL MANAGEMENT - ABDELAZIM, Assem (Human Resource and Leadership Journal, 2022)
Purpose: Globalization has made global changes, and a rapid increase of multinational corporations which has resulted in creating more businesses that have more culturally diverse workforce. Cultural diversity affects the performance of an organization and various conflicts can be occurred because of misunderstandings among the culturally diverse workforce. The purpose of this study is therefore to contribute to the current field of cross-cultural management and how cultural diversity is managed. Methodology: The study investigates four chosen cross-cultural aspects to see how issues within these areas can be minimized. Unique Contribution to Theory and Practice: The knowledge of cultural differences within these aspects will contribute to a better understanding of how these differences can be managed in a Swedish multinational organization with a subsidiary in India.